The development of cortical columns: role of Fragile X mental retardation protein - Bureau, Ingrid (Blackwell Science Inc, 2009)
Neuronal circuits in the brain are complex and precise. Here, I review aspects of the development of cortical columns in the rodent barrel cortex, focusing on the anatomical and functional data describing the maturation of ascending glutamatergic circuits. Projections from layer 4 to layer 3 develop into cortical columns with little macroscopic refinement. Depriving animals of normal sensory experience induces long-term synaptic depression but does not perturb this pattern of development. Mouse models of mental retardation can help us understand the mechanisms of development of cortical columns. Fmr1 knock-out (ko) mice, a model for Fragile X syndrome, lack Fragile X mental retardation protein (FMRP), a suppressor of translation present in synapses. Because FMRP expression is stimulated by neuronal activity, Fmr1-ko mice provide a model to survey the role of sensory input in brain development. Layer 4 to layer 3 projections are altered in multiple ways in the young mutant mice: connection rate is low and layer 4 cell axons are spatially diffuse. Sensory deprivation rescues the connection rate phenotype. The interaction of FMRP and neuronal activity in the development of cortical circuits is discussed.